Translating Utopia - Performing Madagascar. Appunti di viaggio per una traduzione performativa (Mantichora. Italian Journal of Performance Studies, 2020)
This article is part of the theatrical project Towards Madagascar, that the two authors are realizing togheter with the Italian troupe Gli Incauti (www.incauti.org). The project consists in translating and acting the 2004 Lithuanian play Madagaskaras by Marius Ivaskevicius. This paper is a sort of report of the work in progress: the first part concerns a possible theoretical approach for what we call “performative translation” of a play, while the second part presents and explores the play. What the authors experienced in their work is that translating Drama is a performative practice, that differs from the other kinds of literary translation because of its inner expressivity and its necessity of be visualized and performed. The process of translating and playing Madagaskaras offers a precious experience in this sense: it implies not only verbal and contextual translation, but also requires a profound reflection on the possibility to translate national topics, ‘local’ puns, national literary heritage and language. To use George Steiner’s words, we can say that Performing translation is an ‘original recreation’ that faithfully respects the form and the Utopian aim of the original play.